Streamlining door to recanalization processes in endovascular stroke therapy. (5th April 2016) - Aghaebrahim, Amin; Streib, Christopher; Rangaraju, Srikant; Kenmuir, Cynthia L; Giurgiutiu, Dan-Victor; Horev, Anat; Saeed, Yumna; Callaway, Clifton W; Guyette, Francis X; Martin-Gill, Chris; Pacella, Charissa; Ducruet, Andrew F; et al.
Abstract : Background: In acute stroke due to large vessel occlusion, faster reperfusion leads to better outcomes. We analyzed the effect of optimization steps aimed to reduce treatment delays at our center. Methods: Consecutive patients with ischemic stroke treated with endovascular therapy were prospectively analyzed. We divided the patients into pre-optimization (20 April 2012 to 8 October 2013) and post-optimization (9 October 2013 to 29 July 2014) periods. The main interventions included: (1) continuous feedback; (2) standardized immediate emergency department attending to stroke attending communication with interventional team activation for all potential interventions; (3) pre-notification by the emergency medical service; (4) minimizing additional diagnostic testing; (5) direct transport to the CT scanner; (6) transport directly from the CT scanner to the angiography suite. The main metric used to measure improvement was door to groin puncture time (D2P). Results: We included a total of 286 patients (178 pre-optimization, 108 post-optimization). There were no significant differences between major baseline characteristics between the groups with the exception of higher median CT Alberta Stroke Program Early CT Score in the pre-optimization group (p=0.01). Median D2P improved from 105 min pre-optimization to 67 min post-optimization (p=0.0002). Rates of good clinical outcomes (modified Rankin Scale 0–2 at 3 months) were similar in both groups, with a trend toward a better outcome in the post-optimization group in a subgroup analysis of patients with anterior circulation occlusion who received intravenous tissue plasminogen activator. Conclusions: This pilot study demonstrates that D2P times can be significantly reduced with a standardized multidisciplinary approach. There was no significant difference in the rate of 3-month good outcome, which is most likely due to the small sample size and confounding baseline patient characteristics.